Burnout Syndrome in School teachers and University Professors: A Psychometrical and Comparative Analysis from Arequipa City - Arias Gallegos, Walter L. (2019)
In the present study, the manifestations of burnout syndrome in school and university professors living in the city of Arequipa were analyzed comparatively. A total of 413 intentionally selected professors were evaluated, and the Maslach Burnout Inventory was applied. It  yielded adequate levels of reliability for our sample and three factors obtained through confirmatory factorial analysis, confirming the theory of Maslach and Jackson (1981). It was found that there are significant differences in terms of sex, marital status and teaching level of teachers, resulting in higher levels of exhaustion for female teachers at school level and moderate levels of depersonalization for university teachers, in whom negative correlations were obtained regarding the number of children and the  burnout syndrome.